Serum from a Patient with GAD65 Antibody-Associated Limbic Encephalitis Did Not Alter GABAergic Neurotransmission in Cultured Hippocampal Networks - Stemmler, Nelly; Rohleder, Karin; Malter, Michael P.; Widman, Guido; Elger, Christian E.; Beck, Heinz; Surges, Rainer (Frontiers in Neurology, 2015)
Background: Glutamate decarboxylase (GAD) is an intracellular enzyme converting glutamate into GABA. Antibodies (ab) to its isoform GAD65 were described in limbic encephalitis (LE) and other neurological conditions. The significance of GAD65-ab for epilepsy is unclear, but alterations of inhibitory GABAergic neurotransmission may be involved. Here, we investigated the effects of the serum of a female patient suffering from GAD65-ab associated LE on GABAA currents in cultured hippocampal networks. Methods: Spontaneous or evoked postsynaptic GABAA currents were measured in cultured hippocampal neurons prepared from embryonic mice after 11-21 days in-vitro using the patch-clamp technique in the whole-cell mode after incubation with serum of a healthy control or the LE-patient at a final concentration of 1 % for 5-8 hours. Results: Properties of miniature inhibitory postsynaptic currents were not different in cultures treated with control and LE-serum. Likewise, paired-pulse ratio of evoked GABAA currents as a measure of release probability was not different in both conditions. Evoked GABAA currents were significantly depressed during 10 Hz stimulation without significant differences between control and LE-serum treated cultures. Conclusions: In our experimental paradigms, serum of a patient with confirmed GAD65 antibody-associated LE had no apparent effect on GABAergic neurotransmission in murine cultured hippocampal networks. These results challenge the view that the presence of GAD65 antibodies invariably compromise inhibitory network function.